Education and health promotion: a historical retrospect - Focesi Pelicioni, Maria Cecília; Focesi Pelicioni, Andréa (O Mundo da Saúde, 2007)
The present article makes a historical retrospect of educative actions in the health field, especially sanitary education and education in public health, as well as its relationships with Health Promotion. People’s empowerment and active participation - praised by the paradigm of Health Promotion - will be made possible by education for health, as a political formation process for active citizenship preparing individuals and/or groups to take the control and the responsibility by their own health, among others objectives. In the same way, this educative action will have to be one of communication, dialogue if it wants to reach human beings in their historical reality, for only motivated and enabled will them be able to incorporate new meanings, values and practices to improve their quality of life.